Financial market responses to a natural disaster: evidence from credit networks and the Indian Ocean tsunami - Czura, Kristina; Klonner, Stefan (Journal of development economics, 2023)
We examine changes in financial allocations in Rotating Savings and Credit Associations (Roscas), a popular group-based financial institution world-wide, in the aftermath of the 2004 Indian Ocean tsunami. With financial data from locations along the South Indian coast we estimate the causal effect of this major natural disaster on financial flows between occupational groups, the price of credit and other loan characteristics. We find that the supply of funds in these credit networks remained remarkably stable, while demand by small and medium-scale entrepreneurs increased significantly. In response, substantial funds were channeled from wage-employed members and commercial investors to entrepreneurs. We conclude that natural disasters affect individuals with substantial heterogeneity and that the Roscas we study offer more scope for gains from trade in response to a seemingly aggregate shock than commonly assumed for traditional credit and insurance networks.
Online verfügbar 1 November 2022, Artikelversion 25 November 2022
Gesehen am 25.01.2023
Keywords: Indischer Ozean